2020
DOI: 10.1007/s10815-020-01974-5
|View full text |Cite
|
Sign up to set email alerts
|

Is there a critical LH level for hCG trigger after the detection of LH surge in modified natural frozen-thawed single blastocyst transfer cycles?

Abstract: Purpose There is no consensus yet in the literature on an optimal luteinizing hormone (LH) level for human chorionic gonadotrophin (hCG) trigger timing in patients undergoing frozen-thawed embryo transfer (FET) with modified natural cycles (mNC). The objective of our study was to compare the clinical results of hCG trigger at different LH levels in mNC-FET cases. Methods This retrospective study was conducted in Istanbul Memorial Hospital ART and Genetics Center. A total of 1076 cases with 1163 mNC-FET cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…When the dominant follicle reached 15 mm, serum estradiol and LH levels were monitored every 24 h until LH surge was detected. When the endometrial thickness reached above 8 mm and the LH level rose above, a critical threshold level (> 15 IU/L), r-hCG (Ovitrelle, Merck-Serono, Switzerland) was administered [ 14 ]. Frozen embryo transfer was performed 6 days after rhCG administration.…”
Section: Methodsmentioning
confidence: 99%
“…When the dominant follicle reached 15 mm, serum estradiol and LH levels were monitored every 24 h until LH surge was detected. When the endometrial thickness reached above 8 mm and the LH level rose above, a critical threshold level (> 15 IU/L), r-hCG (Ovitrelle, Merck-Serono, Switzerland) was administered [ 14 ]. Frozen embryo transfer was performed 6 days after rhCG administration.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, there is no study comparing different doses of hCG for triggering in modified-NC; in theory, the lowest effective dose to induce ovulation will result in a lower early serum P 4 , which should reduce the risk of endometrial advancement, known to have a negative impact on endometrial receptivity. The place for endocrine monitoring in modified-NC is controversial (51,52). Whether monitoring of serum P 4 and LH levels in modified-NC FET cycles has added clinical value needs to be explored.…”
Section: Modified-ncmentioning
confidence: 99%
“…The study was interrupted prematurely. However, the impact of an impending LH surge on reproductive outcomes in modified-NC is controversial, some reporting a negative impact (66) and others no impact at all (51,52).…”
Section: Comparison Of T-nc Versus Modified-ncmentioning
confidence: 99%
“…On the other hand, studies have also shown that abnormal luteinizing hormone (LH) levels will lead to poor endometrial hyperplasia and affect pregnancy outcomes (14)(15)(16). However, the effects of P and LH levels on pregnancy outcomes in the mNC-thawed embryo transfer (mNC-FET) remain controversial (6,17,18). Therefore, we conducted a retrospective study of the mNC-FET cycles in our reproductive medicine centre at Nanjing Drum Tower Hospital to investigate the relationships between serum P and LH levels before the hCG trigger and clinical pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Since the natural cycles and modified natural cycles do not require ovarian stimulation and meet the physiological requirements of embryo implantation, they can avoid the endometrial synchronization disorder caused by superphysiological levels of oestrogen and have become the most common endometrial preparation protocols ( 4 , 5 ). In modified natural cycles, dominant follicle development is detected by ultrasound and changes in hormone levels are measured to detect the human chorionic gonadotropin (hCG) trigger time, which is especially critical for the correct transformation of the endometrium ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%